2020
DOI: 10.3390/ma13235490
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Properties of Waste Sawdust-Based Lightweight Alkali-Activated Concrete: Experimental Assessment and Numerical Prediction

Abstract: Alkali activated concretes have emerged as a prospective alternative to conventional concrete wherein diverse waste materials have been converted as valuable spin-offs. This paper presents a wide experimental study on the sustainability of employing waste sawdust as a fine/coarse aggregate replacement incorporating fly ash (FA) and granulated blast furnace slag (GBFS) to make high-performance cement-free lightweight concretes. Waste sawdust was replaced with aggregate at 0, 25, 50, 75, and 100 vol% incorporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…Accordingly, in recent years, numerous mathematical predictions and optimisation models have been developed within the research community, including artificial neural networks (ANNs) [ 25 , 26 , 27 ], metaheuristic algorithms [ 28 , 29 ], genetic expression programming (GEP) [ 30 , 31 , 32 , 33 ], adaptive neuro-fuzzy inference systems (ANFIS) [ 34 , 35 , 36 ], and response surface methodology (RSM) [ 37 , 38 , 39 ]. Among them, RSM is one of the best statistical techniques used for data optimization [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in recent years, numerous mathematical predictions and optimisation models have been developed within the research community, including artificial neural networks (ANNs) [ 25 , 26 , 27 ], metaheuristic algorithms [ 28 , 29 ], genetic expression programming (GEP) [ 30 , 31 , 32 , 33 ], adaptive neuro-fuzzy inference systems (ANFIS) [ 34 , 35 , 36 ], and response surface methodology (RSM) [ 37 , 38 , 39 ]. Among them, RSM is one of the best statistical techniques used for data optimization [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…All the designed GPMs specimens containing WCT showed lower drying shrinkage than the one obtained for OPC-based NC. Previous studies indicated that the drying shrinkage characteristics of the alkali-activated geopolymer composites are more complicated than OPC composites due to their complex hydration and shrinkage mechanisms [ 55 , 56 , 57 ]. Among these geopolymer binders, the shrinkage problem of GBFS-based geopolymer systems is particularly prominent, which is significantly higher compared to other geopolymer composites (such as FA, metakaolin, and coal gangue) [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among these geopolymer binders, the shrinkage problem of GBFS-based geopolymer systems is particularly prominent, which is significantly higher compared to other geopolymer composites (such as FA, metakaolin, and coal gangue) [ 56 ]. Some reports indicated that the partial replacement of GBFS by FA can effectively alleviate the shrinkage of the GPMs systems but weaken their strength development [ 22 , 32 , 54 , 55 ]. Therefore, the selection of suitable proportions of the mineral admixtures is very important to optimize the performance of GPMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fraction of aggregates is about 60% to 80% of the concrete total volume [ 7 , 8 ]. Moreover, the preparation of some types of concrete such as light and heavyweight concrete, as well as concrete resistant to sound or vibration, can be achieved through the proper selection of aggregates [ 9 , 10 , 11 , 12 , 13 ]. In developing almost all types of special concrete, selecting the proper aggregates, and manipulating their size distributions are two important steps.…”
Section: Introductionmentioning
confidence: 99%